Pelatihan Minp Maping Bagi Guru Untuk Membuat Bahan Ajar Alternatif Bagi Siswa Mi Muhammadiyah Balung - Rofi, Sofyan; Fatkhurrochman , Henri; Kusumawati , Dahani (Universitas Muhammadiyah Jember, 2023)
Teaching materials become basic needs in the learning process in all educational environments both at home, school, and community. The availability of flexible and effective teaching materials can encourage good student learning outcomes as a representation of the effectiveness and efficiency of the learning process, especially in schools. The modernization era has a positive impact with the availability of applications and programs in making teaching materials such as canva, cohorts, hotpotatos, and mind mapping applications ranging from free to paid such as free mind, lucid chart, Ayoa, and mindomo. The need for teachers in providing quality teaching materials must certainly be supported by qualified competencies, especially in the field of information technology as an effort to design and manufacture mind mapping-based materials. The main function of mind mapping is to map the concept of subjects to make it simpler or simpler and have ease of use in understanding and mastering the learning material being studied. The main nature of simple mid-mapping with a multi-color display will affect student learning motivation, especially at the elementary school / madrasah level. The ability in this field for teachers is an aspect that needs to be developed holistically and comprehensively as a reflection of the dimensions of this training which took place at MI Muhammadiyah Balung as an effort to manifest cooperation between the two parties. Professionalism. This activity is carried out as a program of community service activities packaged in the form of training, as an effort to help the capacity to increase and develop teacher competencies in the realm of hard skills. The concrete impact is that teachers can create teaching materials based on the concept of mind maping, as a supporter of alternative teaching materials for students in realizing learning effectiveness and efficiency